Antibacterial activity of Nickel-doped ZnO/MWCNTs hybrid prepared by sol–gel technique - AL-Jawad, Selma M.H.; Shakir, Zahraa S.; Ahmed, Duha S. (European physical journal. Applied physics, 2021)
ZnO/MWCNTs and Ni-doped ZnO/MWCNTs hybrid with different concentration of Nickel element was prepared by using sol–gel technique. The produced samples were characterized by using X-ray diffraction analysis (XRD), energy dispersive X-ray spectroscopy (EDS), Fourier-transform infrared spectroscopy (FTIR), field-emission scanning electron microscopy (FE-SEM), and UV–vis spectroscopy. The polycrystalline nature with hexagonal wutzite structure of ZnO/MWCNTs and Ni-doped ZnO/MWCNTs hybrid was shown by X-ray diffraction. The hybrid nanostructure's crystalline size increased from 23.73 nm to 34.59 nm. Furthermore, UV-Vis spectroscopy reveals a significant decrease in band gap values from 2.97 eV to 2.01 eV. The FE-SEM analysis, on the other hand, confirms the formation of spherical shapes of ZnO NPs diffused on the surface of MWCNTs. The antibacterial activity showed that the inhibition zone of Ni doped-ZnO/MWCNTs hybrid was 28.5 mm for E. coli and 26.5 mm for S. aureus bacteria, respectively.